Consistent or balanced? On the dynamics of voluntary contributions - Carlo Gallier; Christiane Reif; Daniel Römer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
We investigate the dynamic effects of a charitable lottery and an income tax on donations. The analysis is based on a two-round dictator game with the subject's charity of choice as recipient and additional incentives in the first round only. The immediate effect of a charitable lottery leads to higher contributions and we cannot find substantial crowding out of voluntary contributions in the presence of an income tax. These economic interventions weakly spill-over to the subsequent donation decisions without additional incentives. Our results suggest the presence of consistency seeking behaviour. This is especially true for a subgroup of participants with a rule-based mind-set and our research shows the importance of the subjects' moral framework in the context of dynamic pro-social behaviour.
urn:nbn:de:bsz:180-madoc-370709; More recent version: http://hdl.handle.net/10419/110598
Keywords: C91; D64; 330; charitable giving; laboratory experiment; lottery; tax; voluntary contribution mechanism